PHARMACEUTICAL GELS - Syeda Yamna Zia (Baqai Journal of Health Sciences)
Gels are three-dimensional semisolid systems formed by the interlinking of gelling agent and dispersion medium. They are non-invasive, less greasy, non-toxic, and inert to food and drugs. They have minimum side effects, hence becoming a reason for increasing patient compliance and topic of interest over the last few decades. Various methods of preparations of gels have been designed by incorporating variety of polymers in dispersion mediums to meet the needs of different applications. This shows their flexibility in the formulation. Their structures, characteristics, properties, methods of preparation, components, classification and stability parameters have been discussed. Thus, gives an idea about the importance of gels in biomedical applications